Guarding the Nation: A Comprehensive Look at State Cybersecurity Measure - SPĂTARU, Marian-Emilian; BARCAN, Alexandru (International Conference on Cybersecurity and Cybercrime, 2023)
In a continuously evolving world, technology has not been left out of the process which consists of studies and research done by specialists in the field of cyber technology. Although the latter has brought along benignant effects in society, it can be considered a controversial domain due to those effects that can be used against the public safety and national security. Cyber-attacks & Cyber terrorism are just two of them, usually countered by Cyber intelligence, OSINT security, Cyber risk management. These actions are coordinated by different intelligence services such as: Federal Bureau of Investigation – FBI, Romanian Intelligence Service – SRI, Federal Security Service – FSB, while they have to cooperate with civilians, due to a shortage of employees. The lack of qualified staff on the following domain: awareness of the different types of cyber-attack, such as malware, web-based attacks, phishing, web application attacks, spam, distributed denial of service (DDoS), identity theft, data breach, insider threat, botnets, physical manipulation, damage, theft and loss, information leakage, ransomware, cyber-espionage, industrial espionage and crypto jacking, reaches an amount of 7.659 officials that are needed in this area.